Active material and manufacturing method thereof, and electrode mixture, electrode, and battery containing the same

By coating the core material particles of the active material in solid sodium batteries with specific oxygen-containing compounds, the resistance of the positive electrode is reduced, addressing the issue of insufficient discharge capacity in conventional electrodes.

JP2025038807APending Publication Date: 2025-03-19MITSUI MINING & SMELTING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
JP2023145639
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Conventional electrodes in solid sodium batteries exhibit high resistance, leading to insufficient discharge capacity due to the formation of high resistance layers.

Method used

An active material with core material particles coated with a second oxygen-containing compound containing elements such as sulfur, phosphorus, niobium, tantalum, or zirconium is used for the positive electrode, which reduces the formation of high resistance layers.

Benefits of technology

The use of the coated active material significantly reduces the resistance of the positive electrode, enhancing the discharge capacity and overall performance of the solid sodium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038807000001
    Figure 2025038807000001
Patent Text Reader

Abstract

To provide an active material for use in the manufacture of a positive electrode having low resistance.SOLUTION: An active material includes a core particle and a coating portion disposed on the surface of the core particle. The core particle contains a first oxide containing elemental sodium (Na). The coating portion contains a second oxygen-containing compound containing elemental A. The elemental A is at least one selected from elemental sulfur (S), elemental phosphorus (P), elemental niobium (Nb), elemental tantalum (Ta), and elemental zirconium (Zr).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active material and a method for producing the same, and also to an electrode mixture, an electrode, and a battery each containing the active material. [Background technology]

[0002] In recent years, secondary batteries have been attracting attention as an effort to prevent global warming by reducing CO2 emissions. Various lithium-ion batteries have been proposed as secondary batteries, but concerns have been raised about the amount of lithium resources available for lithium-ion batteries. As a result, sodium-ion batteries, especially solid-state sodium batteries, which offer greater safety, have been attracting attention.

[0003] For example, Non-Patent Document 1 describes a method using a positive electrode made of NaCrO2, a solid electrolyte made of Na3PS4, and a negative electrode made of Na 15 An all-solid-state cell using Sn4 is described. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Akitoshi Hayashi et al.,J.Power Sources 2014,258,420-423 Summary of the Invention [Problem to be solved by the invention]

[0005] The inventors conducted research aimed at improving the performance of solid-state sodium batteries and discovered that the use of conventional electrodes results in high positive electrode resistance, which can lead to problems such as insufficient discharge capacity.

[0006] It is therefore an object of the present invention to provide an active material for the manufacture of positive electrodes having low resistance. [Means for solving the problem]

[0007] The present invention provides an active material having a core particle and a coating portion disposed on a surface of the core particle, The core particles include a first oxide containing sodium (Na), the coating portion contains a second oxygen-containing compound containing an A element, The active material is provided in which the element A is at least one selected from the group consisting of sulfur (S), phosphorus (P), niobium (Nb), tantalum (Ta), and zirconium (Zr).

[0008] The present invention also provides a method for producing an active material having a core particle and a coating portion disposed on a surface of the core particle, comprising the steps of: The core particles include a first oxide containing sodium (Na), The method includes a step of mixing a second oxygen-containing compound containing an A element with the core particles, The present invention provides a method for producing an active material, wherein the element A is at least one selected from the group consisting of sulfur (S), niobium (Nb), tantalum (Ta), and zirconium (Zr). Effect of the Invention

[0009] According to the present invention, an active material is provided for use in the manufacture of low resistance positive electrodes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will now be described based on its preferred embodiments. The present invention relates to a battery active material and a method for producing the same. The active material of the present invention can be preferably used as an active material for a sodium ion battery, and particularly as a positive electrode active material for the battery. The active material of the present invention has a core particle and a coating portion disposed on the surface of the core particle. The core particle is a portion that occupies the majority of the active material, and contains a first oxide containing sodium (Na) element as described later. The coating portion contains a second oxygen-containing compound containing element A as described later. The first oxide and the second oxygen-containing compound will be described in detail later. By disposing the coating portion on the surface of the core particle, for example, it is possible to suppress the formation of a high resistance layer that occurs between the core particle and an electrolyte due to contact between the two. The formation of a high resistance layer is one of the causes of an increase in the resistance of an electrode. It is known that a high resistance layer is formed when the chemical potential of the active material and the chemical potential of the electrolyte are significantly different ("Development of All-Solid-State Secondary Battery", Science & Technology Co., Ltd., June 29, 2007, pp. 198-210). Therefore, in order to suppress the formation of a high resistance layer, it is preferable to use a compound whose sodium ion electrochemical potential is close to that of the core particle as the coating portion in the active material. Furthermore, it is preferable that the compound contained in the coating portion has ion conductivity. By using an active material having such a coating portion, the generation of a high resistance layer is suppressed, and the resistance of the electrode (particularly the positive electrode) can be reduced.

[0011] [Covering part] In the active material of the present invention, the coating portion preferably contains a second oxygen-containing compound containing the element A. This is because the resistance of the positive electrode produced using the active material of the present invention can be effectively reduced. From this viewpoint, the element A is preferably at least one selected from the group consisting of sulfur (S), phosphorus (P), niobium (Nb), tantalum (Ta), and zirconium (Zr), and the element A is more preferably at least one selected from the group consisting of sulfur (S), phosphorus (P), and niobium (Nb), and further preferably at least one selected from the group consisting of sulfur (S) and phosphorus (P). The above-mentioned elements A have in common that they are elements that have the function of reducing the difference between the chemical potential of the active material and the chemical potential of the electrolyte, thereby suppressing the formation of a high-resistance layer between the two.

[0012] As used herein, the term "oxygen-containing compound" refers to a compound that contains the element oxygen (O).

[0013] Examples of the second oxygen-containing compound include sulfates, hydrogen sulfates, sulfites, and hydrogen sulfites, which are compounds containing an S element; phosphates, monohydrogen phosphates, dihydrogen phosphates, phosphites, hydrogen phosphites, and dihydrogen phosphites, which are compounds containing a P element; niobates, which are compounds containing an Nb element; tantalates, which are compounds containing a Ta element; and zirconates, which are compounds containing a Zr element. These oxides can be used alone or in combination of two or more. Among them, from the viewpoint of making the effect of reducing the resistance of the electrode by the coating portion more noticeable, it is preferable that the second oxygen-containing compound is a sulfate.

[0014] The second oxygen-containing compound may contain elements other than the A element and the oxygen (O) element. Examples of the other elements include alkali metal elements such as lithium (Li), sodium (Na), potassium (K) and rubidium (Rb). Among them, the second oxygen-containing compound preferably contains sodium (Na). When the second oxygen-containing compound contains sodium (Na), the active material of the present invention becomes suitable as an active material for a sodium ion battery, particularly as a positive electrode active material for a sodium ion battery. Examples of the second oxygen-containing compound containing Na element include sodium salts of the various oxides mentioned above.

[0015] In summary, it is particularly preferred that the second oxygen-containing compound is sodium sulfate.

[0016] The amount of the second oxygen-containing compound may be, for example, 0.1 mass % or more, 1.0 mass % or more, or 3.0 mass % or more, based on the mass of the active material. The amount of the second oxygen-containing compound may be, for example, 10.0% by mass or less, 8.0% by mass or less, or 7.0% by mass or less, based on the mass of the active material. By setting the content of the second oxygen-containing compound relative to the core particle within the above range, the effect of reducing resistance by the coating portion can be made more significant.

[0017] Furthermore, the second oxygen-containing compound is preferably contained in an amount of, for example, 40 mass% or more, more preferably 60 mass% or more, even more preferably 80 mass% or more, and even more preferably 95 mass% or more, relative to the mass of the coating portion. The closer the proportion of the second oxygen-containing compound in the coating portion is to 100 mass %, the more preferable it is since the resistance of the electrode can be reduced more.

[0018] The second oxygen-containing compound is preferably present on the surface of the core particle as (I) particles, as aggregated particles formed by aggregation of (II) particles, or as (III) a layer. "Present in the form of a layer" means that the second oxygen-containing compound is present with a certain thickness, and may be present on the entire surface of the core particle or may be present partially in the form of islands. In this specification, any of the above embodiments (I) to (III) is encompassed by "a coating portion containing a second oxide is formed."

[0019] When the second oxygen-containing compound is present on the surface of the core particle in the above-mentioned form (III), the thickness of the coating portion is preferably adjusted within a predetermined range. In particular, from the viewpoint of reliably obtaining the effect of the coating portion, the thickness of the coating portion may be 1.0 nm or more, 2.0 nm or more, or 5.0 nm or more. In addition, from the viewpoint of suppressing an increase in the resistance of the electrode caused by the resistance of the coating portion itself, the thickness of the coating portion may be 100 nm or less, 50 nm or less, or 30 nm or less. The thickness of the coating portion may be uniform or may not be uniform. The thickness of the coating portion can be measured, for example, by X-ray photoelectron spectroscopy (XPS). If necessary, the thickness can also be measured by combining a scanning transmission electron microscope (STEM) and Auger electron spectroscopy (AES) for observation.

[0020] The coating portion may contain a compound other than the second oxygen-containing compound. Examples of such compounds include compounds containing carbon (C) such as sodium carbonate, and compounds containing silicon (Si) such as silicon dioxide. These compounds may be used alone or in combination of two or more.

[0021] The surface of the core particle may have a portion where the coating portion is not present. The coverage rate of the coating portion with respect to the entire surface of the core particle is, for example, preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and even more preferably 40% or more. The fact that the surface of the core particle is covered by the coating portion can be confirmed, for example, by observing the surface of the core particle by combining X-ray photoelectron spectroscopy (XPS) and, if necessary, a scanning transmission electron microscope (STEM) or energy dispersive X-ray analysis (EDS) in the same manner as above, as well as by Auger electron spectroscopy (AES).

[0022] [Core particles] The core particles contain a first oxide containing sodium (Na). Any first oxide may be used as long as the core particles function as an active material. In particular, it is preferable that the first oxide contains a transition metal element, that is, the first oxide is an oxide of a transition metal element. Examples of such transition elements include at least one of Fe, Ni, Co, Mn, V, Cr, Ti, and Cu. Examples of the first oxide include layered compounds, spinel compounds, and polyanion compounds.

[0023] The layered compound and the spinel compound include, for example, Nax Examples include MO2 (0 < x ≤ 1, where M is at least one of Fe, Ni, Co, Mn, Cr, V, Ti, and Cu), etc. In one example, the first oxide is Na x a layered sodium metal oxide of MO2 (0.5 ≤ x ≤ 1, where M is at least one of Co, Mn, Fe, Ni, Ti, Cr, V, and Cu). In another example, the first oxide is Na x a P2-type layered sodium metal oxide of MO2 (0.5 ≤ x ≤ 1, where M is at least one of Co, Mn, Fe, Ni, Ti, Cr, V, and Cu). In another example, the first oxide is Na x an O3-type layered sodium metal oxide of MO2 (0.8 ≤ x ≤ 1, where M is at least one of Co, Mn, Fe, Ni, Ti, Cr, V, and Cu). In another example, the first oxide is Na x a layered sodium manganese oxide of MnO2 (0 < x ≤ 1). In another example, the first oxide is Na x M’ 1-y M y a mixed layered oxide of M’O2 (0 < x ≤ 1, 0 < y < 1, where M and M’ are each independently at least one of Co, Mn, Fe, Ni, Ti, Cr, V, and Cu, and M is different from M’). Specific examples of the layered compound include NaMnO2, Na 0.5 CoO2, Na 0.67 CoO2, Na 0.67 Co 0.67 Mn 0.33 O2, Na 0.67 Ni 0.33 Mn 0.67 O2, Na 0.67 Co 0.6 Mn 0.4 O2, Na 0.67 Co 0.55 Mn 0.45 O2, Na 0.67 Co 0.5 Mn 0.5 O2, Na 0.67 Co 0.50 Mn 0.33 Ti 0.17O2, Na 0.6 MnO2, NaNi 0.4 Co 0.2 Mn 0.4 O2 and NaNi 0.33 Fe 0.33 Mn 0.33 O2, etc.

[0024] The polyanion type compound includes, for example, sodium transition metal phosphate crystals containing Na (sodium), M (M is at least one transition metal element selected from Cr, Fe, Ni, Co, Mn, and V), P (phosphorus) and O (oxygen). Specific examples of sodium transition metal phosphate crystals include Na3V2(PO4)3, NaFePO4, NaFeP2O7, Na2MP2O7 (M is at least one of Fe, Ni, Co, and Mn), Na4M3(PO4)2P2O7 (M is at least one of Fe, Ni, Co, and Mn), Na 3.64 Ni 2.18 (P2O7)2, Na3Ni3(PO4)2P2O7, etc. The sodium transition metal phosphate crystal is preferred because it has a high capacity and is excellent in chemical stability. Among them, triclinic crystals belonging to the space group P1 or P-1, particularly those of the general formula Na a M b P2O c A crystal represented by the formula (1.2≦a≦2.8, 0.95≦b≦1.6, 6.5≦c≦8, M is at least one of Fe, Ni, Co and Mn) is preferred due to its excellent cycle characteristics. Another example of a polyanion type compound is Na2Fe2(SO4)3.

[0025] The first oxide may be doped with small amounts of other elements or impurities as necessary to adjust or optimize the electrochemical properties of the active material. For example, the metal elements contained in the first oxide may be doped by partial substitution with other metal elements. The other metal elements may include transition metal elements such as Fe, Co, Ni, Mn, Ti, Cr, Cu, and V; and typical metal elements such as Mg, Al, and Sb.

[0026] When the active material of the present invention is used in a sodium ion battery, it is preferable that the first oxide is substantially free of lithium element from the viewpoint of cost reduction. Here, "substantially free of lithium element" means that the content of lithium element in the first oxide is preferably 5 mass % or less, more preferably 3 mass % or less, and even more preferably 1 mass % or less.

[0027] [Active material] As described above, the active material of the present invention has a coating portion containing a second oxygen-containing compound. Due to this, in the X-ray diffraction pattern of the active material of the present invention measured by an X-ray diffractometer using CuKα1 radiation, a peak derived from the second oxygen-containing compound is observed. For example, when the second oxygen-containing compound is sodium sulfate, a peak is observed in the range of 2θ of 18° to 20°.

[0028] The active material of the present invention is generally in the form of particles, 50 That is, the volume cumulative particle size at 50% of cumulative volume measured by a volume particle size distribution measurement method obtained by a laser diffraction scattering type particle size distribution measurement method is, for example, preferably 0.5 μm or more, more preferably 1.0 μm or more, further preferably 2.0 μm or more, and particularly preferably 5.0 μm or more. 50 is preferably, for example, 50.0 μm or less, more preferably 40.0 μm or less, and even more preferably 30.0 μm or less. 50 By setting the content of the cation in the above range, it is possible to reduce the resistance when ions such as sodium ions diffuse into the particles of the active material.

[0029] The active material of the present invention can be made into an electrode mixture by mixing it with a solid electrolyte and a conductive material. This electrode mixture is useful for forming an electrode (particularly a positive electrode) of a battery. The solid electrolyte is not particularly limited as long as it has the desired ion conductivity, and for example, an oxide solid electrolyte or a sulfide solid electrolyte can be used. As the conductive material, for example, a conductive substance made of a carbon material can be used.

[0030] The electrode mixture of the present invention can be mixed with a binder and a solvent to form a coating composition. This coating composition is useful from the viewpoint of forming an electrode (particularly a positive electrode) by coating the coating composition on the surface of a current collector, for example. An electrode can be formed on the surface of the current collector by coating the coating composition on the surface of the current collector, drying the coating film formed thereby, and removing the solvent. The electrode thus formed contains the electrode mixture and binder described above. As the binder and solvent contained in this coating composition, those conventionally used in the technical field can be used without any particular limitation.

[0031] The battery containing the active material of the present invention may be, for example, a battery having a structure including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, that is, a solid-state battery. When the active material of the present invention is a positive electrode active material, the positive electrode layer contains the composite active material of the present invention. The solid electrolyte contained in the solid electrolyte layer is not particularly limited as long as it has the desired ion conductivity, and for example, an oxide solid electrolyte or a sulfide solid electrolyte can be used. As described above, the active material of the present invention is preferably used as an active material for a sodium ion battery. In addition, it is more preferable that the sodium ion battery contains a sulfide solid electrolyte, because the active material has a coating portion, which can make the effect of reducing the resistance of the electrode more remarkable.

[0032] [Method of producing active material] The method for producing an active material of the present invention includes a step of mixing the second oxygen-containing compound containing element A with the core particles (hereinafter also referred to as a "mixing step"). Details of the core particles and the coating portion are as described above. The core particles may be commercially available products, or may be produced by a production method including a raw material mixing step, a wet grinding step, a granulation step, a firing step, a heat treatment step, a washing / drying step, and a grinding step, although this production method is merely a preferred example and is not intended to be limiting.

[0033] The mixing of the second oxygen-containing compound and the core particles in the mixing step may be dry mixing or wet mixing. However, since the wet mixing requires a drying step after mixing, it is preferable to dry mix the second oxygen-containing compound and the core particles from the viewpoint of reducing costs and preventing deterioration of the coating portion during the drying step. Dry mixing is preferably carried out under a state in which shear force, compression force and / or impact force is applied. By adopting such a dry mixing method, a coating portion can be firmly formed on the surface of the core material particles. For example, a dry particle composite device (Nobilta (registered trademark) manufactured by Hosokawa Micron Corporation) can be used for dry mixing. Dry mixing can also be carried out by other methods, such as mortar mixing.

[0034] The above-described embodiment of the present invention encompasses the following technical ideas. [1] An active material having a core particle and a coating portion disposed on the surface of the core particle, The core particles include a first oxide containing sodium (Na), the coating portion contains a second oxygen-containing compound containing an A element, The active material, wherein the element A is at least one selected from the group consisting of sulfur (S), phosphorus (P), niobium (Nb), tantalum (Ta), and zirconium (Zr). [2] The active material according to [1], wherein the second oxygen-containing compound contains elemental sodium (Na). [3] The active material according to [1] or [2], wherein the second oxygen-containing compound is a sulfate. [4] The active material according to any one of [1] to [3], wherein the second oxygen-containing compound is sodium sulfate. [5] The active material according to any one of [1] to [4], wherein the first oxide is an oxide of a transition metal element. [6] The active material according to any one of [1] to [5], which is for use in a sodium ion battery. [7] An electrode mixture comprising the active material according to any one of [1] to [6]. [8] An electrode comprising the electrode mixture according to [7] and a binder. [9] A battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, A battery, wherein the positive electrode layer contains the active material according to any one of [1] to [6].

[10] A method for producing an active material having a core particle and a coating portion disposed on a surface of the core particle, comprising: The core particles include a first oxide containing sodium (Na), The method includes a step of mixing a second oxygen-containing compound containing an A element with the core particles, The method for producing an active material, wherein the element A is at least one selected from the group consisting of sulfur (S), niobium (Nb), tantalum (Ta), and zirconium (Zr).

[11] The manufacturing method according to

[10] , wherein in the step, a second oxygen-containing compound and the core particles are dry-mixed. EXAMPLES

[0035] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0036] Example 1 (1) Preparation of core particles The core particles were prepared in the following manner. First, MnO2 was fired at 600°C in air for 10 hours to obtain Mn2O3. Next, Mn2O3 and Na2CO3 were mixed in a molar ratio of 1:1 and mixed in a mortar to obtain a mixture. This mixture was placed in a tubular furnace and fired at 800°C in an argon atmosphere for 24 hours, and then crushed in a mortar to obtain core particles represented by the composition formula NaMnO2. (2) Formation of the coating The core particles and sodium sulfate were each dried overnight at 150°C under a dry air atmosphere. Next, 40g of the dried core particles and 2.0g of dried sodium sulfate were mixed using a NOB-MINI dry particle composite device manufactured by Hosokawa Micron Corporation. Mixing was performed for 90 minutes with a rotor rotation speed of 6000ppm. As a result, sodium sulfate was attached to the surface of the core particles to obtain an active material having a coating portion containing sodium sulfate. The mass ratio of the second oxygen-containing compound (sodium sulfate) to the mass of the active material was 4.8% by mass.

[0037] (3) Battery construction The active material obtained above, a solid electrolyte (Na3PS4), and a conductive material (VGCF (registered trademark) manufactured by Resonac Holdings Inc.) were mixed in a mortar in a mass ratio of active material:solid electrolyte:conductive material=36:55:9 to prepare a positive electrode mixture powder. Furthermore, an active material (HC (hard carbon)) and a solid electrolyte (Na3PS4) were mixed in a mortar at a mass ratio of active material:solid electrolyte=50:50 to prepare a negative electrode mixture powder. A PP cylinder (opening inner diameter 10.5 mm) with the lower opening blocked with an electrode (made of SUS) was used. 50 mg of solid electrolyte (Na3PS4) powder was poured into the cylinder through the upper opening. Next, the upper opening of the cylinder was sandwiched between electrodes and uniaxially pressed at 180 MPa to produce a solid electrolyte layer consisting of a pellet with a diameter of 10.5 mm. The upper electrode was temporarily removed, 18.3 g of the positive electrode mixture powder was inserted into the cylinder, and the upper electrode was then reinstalled. The cylinder was turned upside down, the newly upper electrode was temporarily removed, 20 mg of the negative electrode mixture powder was inserted, and the upper opening of the cylinder was then sandwiched between the electrodes and uniaxially pressed at 550 MPa to compress the positive electrode mixture powder, solid electrolyte layer, and negative electrode mixture powder. Next, the upper and lower electrodes were clamped with a C-clamp and restrained at 4 N m to fabricate a battery (solid-state sodium secondary battery). The fabrication of the battery was carried out in a glove box filled with Ar with an average dew point of -60°C.

[0038] Example 2 An active material and a battery were produced in the same manner as in Example 1, except that the core particles and sodium sulfate were mixed in a mortar instead of NOB-MINI.

[0039] Comparative Example 1 An active material and a battery were produced in the same manner as in Example 1, except that the step (2) was not carried out and the core particles were not coated.

[0040] Comparative Example 2 An active material was prepared in the same manner as in Comparative Example 1. A battery was prepared in the same manner as in Comparative Example 1, except that a negative electrode mixture powder was prepared by using NaCrO2 instead of NaMnO2 as the positive electrode active material and metal Sn instead of HC as the negative electrode active material.

[0041] 〔evaluation〕 The active materials and batteries obtained in the respective Examples and Comparative Examples were evaluated as follows.

[0042] [Active material D 50 〕 The particle size distribution of the active materials obtained in each of the Examples and Comparative Examples was measured using a Microtrac S3500 (manufactured by Microtrac). From the obtained volume-based particle size distribution chart, the volume cumulative particle size D at 50% cumulative volume was 50 The results are shown in Table 1.

[0043] [Initial charge / discharge capacity and AC impedance] The initial charge / discharge capacity and AC impedance R1 of the batteries obtained in the Examples and Comparative Examples were measured as follows. At 25°C, the battery was charged at a constant current of 0.067C to 3.5V, and after the voltage reached 3.5V, it was charged at a constant voltage of 3.5V, and was charged by CCCV mode with the current value reaching 0.0167C as the termination point. It was then discharged by CC mode at 0.067C to 1.8V. This charge / discharge cycle was repeated a total of three times, and finally it was charged by CC mode at 0.067C to 2.7V. The AC impedance R1 of this battery was measured using a Solartron 1255B (manufactured by Toyo Corporation). In addition, the charge capacity and discharge capacity in the first charge / discharge cycle were measured, and these were taken as the initial charge capacity and initial discharge capacity. These results are shown in Table 1. In Table 1, "charge / discharge efficiency" indicates the percentage of the initial discharge capacity relative to the initial charge capacity, and "-" indicates not measured. In addition, the AC impedance R1 of Comparative Example 1 was too large to measure accurately, so it is listed in Table 1 as "about 20,000."

[0044] [Table 1]

[0045] As is clear from Table 1, the battery of Example 1 made using an active material having a coating layer containing sodium sulfate has a significantly lower AC impedance R1 and a larger initial charge capacity, initial discharge capacity, and charge / discharge efficiency than the battery of Comparative Example 1 made using an active material not having the coating layer. Also, it is found that Example 2, in which the core particles and sodium sulfate were mixed in a mortar, also yielded a battery with a large initial charge capacity, initial discharge capacity, and charge / discharge efficiency in a well-balanced manner.

Claims

1. An active material having a core particle and a coating portion disposed on a surface of the core particle, The core particles include a first oxide containing sodium (Na), the coating portion includes a second oxygen-containing compound containing an A element, The active material, wherein the element A is at least one selected from the group consisting of sulfur (S), phosphorus (P), niobium (Nb), tantalum (Ta), and zirconium (Zr).

2. The active material of claim 1 , wherein the second oxygen-containing compound contains elemental sodium (Na).

3. The active material of claim 1 , wherein the second oxygen-containing compound is a sulfate.

4. 3. The active material of claim 2, wherein the second oxygen-containing compound is sodium sulfate.

5. 2. The active material of claim 1, wherein the first oxide is an oxide of a transition metal element.

6. The active material according to claim 1 , which is for a sodium ion battery.

7. An electrode mixture comprising the active material according to claim 1 .

8. An electrode comprising the electrode mixture according to claim 7 and a binder.

9. A battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, A battery, wherein the positive electrode layer comprises the active material according to claim 1 .

10. A method for producing an active material having a core particle and a coating portion disposed on a surface of the core particle, comprising the steps of: The core particles include a first oxide containing sodium (Na), The method includes a step of mixing a second oxygen-containing compound containing an A element with the core particles, The method for producing an active material, wherein the element A is at least one selected from the group consisting of sulfur (S), niobium (Nb), tantalum (Ta), and zirconium (Zr).

11. The method according to claim 10, wherein in the step, the second oxygen-containing compound and the core particles are dry-mixed.

Citation Information

Cited By

  • Coated particles and method for manufacturing same

    WO2026186708A1